PENGARUH KEPEMIMPINAN, DISIPLIN KERJA DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PT. PLN (persero) UP3 DUMAI - ,Machasin, Arif Rahman ,Susi Hendriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of leadership, work discipline and competence on the performance of employees of PT. PLN (Persero) UP3 Dumai, totaling 35 employees. While the samples in this study were taken using the saturated sample method and obtained as many as 35 employees. This study uses multiple linear regression with the help of the SPSS program to test the hypothesis. The results of the study show that leadership has a significant positive effect on performance. Work discipline has a significant positive effect on performance. Competence has a significant positive effect on performance. The results of the study show that simultaneously or jointly have an effect on performance. Keywords: Work stress, Work Discipline, Motivation and Employee Performance